(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Introduction: Open bite malocclusion is one of the most difficult dentofacial deformities to treat. Although this type of malocclusion can occur unilaterally or bilaterally in the buccal segments. It is mostly seen in the anterior segment where there is no incisal contact and vertical overlap of the lower incisors by the uppers. Objectives: The study was aimed to find out the incidence of open bite malocclusion and their pre and post treatment evaluation of the treated cases and also compare the result of two study groups (skeletal open bite and dental open bite). Methods: A total number of 31 patients with open bite malocclusion out of 1372 patients reported to Department of Orthodontics, Dhaka Dental College and Hospital for treatment. Out of them 21 patients were included in this study with mean age 22±5.4, who successfully completed treatment. Of them 14 were included in the dental group and 07 in the skeletal group. Pre treatment history, clinical examination along with pre and post-treatment photographs, study models and lateral cephalograms were used to compare the treatment outcome between the two study groups. Results: The incidence of open bite was 2.3%. Out of 21 open bite samples 14 were of dental type and the rest 07 were of skeletal type. 47.6% open bite had Angles Class I malocclusion, 42.9% were Class II and 9.5% were Class III. Cephalometric analysis of vertical measurements showed that the mandibular plane angle, palatal plane angle and SNA angle significantly decreased from pre-treatment to post-treatment (p<0.05) in both groups . Gonial angle remains unchanged. Cephalometric analysis of the linear and dental measurements showed increased upper face height, posterior facial height and inter-incisal angle. Soft tissue evaluation on cephalometry showed significant decrease of esthetic plane and interlabial gap. A statistically significant mean difference was found in case of negative overbites among the patients with dental group (p<0.001). Less time was required for completion of treatment in dental group and prognosis was significantly better (p<0.05) Conclusion: The result of the present study indicates that the treatment period and wear time of appliance in dental type was shorter than skeletal type. Both groups showed significant improvement though prognosis was better in dental type of open bite cases. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16156 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 1-7